The Oxford Handbook of Leadership 2012
DOI: 10.1093/oxfordhb/9780195398793.013.0002
|View full text |Cite
|
Sign up to set email alerts
|

The Attributes of Successful Leaders: A Performance Requirements Approach

Abstract: This chapter explores the attributes of successful leaders from the perspective of a performance requirements approach, providing a broad overview of determined factors within the context of performance requirements of successful leaders. It describes three broad domains of leadership requirements: cognitive, social, and motivational. The survey of leader performance requirements summarizes the conceptual basis for an array of attributes, arranged in discrete sets, which are likely to differentiate successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
0
10
0
2
Order By: Relevance
“…Furthermore, the propensity to emerge as a leader can be partially explained by one's cognitive ability, motives and values, gender, physical features, and so forth (Judge & Long, 2012;Reitan & Stenberg, 2019;Zaccaro, Kemp, & Bader, 2004;Zaccaro, LaPort, & Jose, 2013;Zaccaro, Green, Dubrow, & Kolze, 2018). For example, Wai's (2013Wai's ( , 2014 retrospective studies based on the longitudinal data of groups of American elite individuals, including the top leaders in business and politics, showed that a significant percentage of these elite leaders or experts were found to be in the top 1% of cognitive ability at an early age.…”
Section: Individual Differences Foundation For Leader Developmentmentioning
confidence: 99%
“…Furthermore, the propensity to emerge as a leader can be partially explained by one's cognitive ability, motives and values, gender, physical features, and so forth (Judge & Long, 2012;Reitan & Stenberg, 2019;Zaccaro, Kemp, & Bader, 2004;Zaccaro, LaPort, & Jose, 2013;Zaccaro, Green, Dubrow, & Kolze, 2018). For example, Wai's (2013Wai's ( , 2014 retrospective studies based on the longitudinal data of groups of American elite individuals, including the top leaders in business and politics, showed that a significant percentage of these elite leaders or experts were found to be in the top 1% of cognitive ability at an early age.…”
Section: Individual Differences Foundation For Leader Developmentmentioning
confidence: 99%
“…Hence, having a full assessment before making any conclusive decisions is preferred and recommended (Pfeifer, 2013;Susman, 2020). Moreover, Zaccaro et al (2012) recommend flexibility, i.e., having the readiness and ability to respond promptly in different situations. While Yukl (2008) stresses proactivity in taking actions to affect results.…”
Section: Leaders' Traits and Skillsmentioning
confidence: 99%
“…A person's leader identity refers to self-conceptualization as a leader (DeRue & Ashford, 2010). This self-conceptualization can be influenced by their personality traits, skills, or knowledge related to leadership (Hogan & Judge, 2012;Judge et al, 2002;Zaccaro et al, 2004Zaccaro et al, , 2013Zaccaro et al, , 2018, its interaction with their leader identity overall (Lord & Hall, 2005;Miscenko et al, 2017), leader self-efficacy (Hannah et al, 2012), their desire for prestige or dominance (Cheng et GROUP MEMBERS PURSUE LEADERSHIP OPPORTUNITIES 6 al., 2013;McClanahan et al, 2021), or differences in their motivation to lead (Badura et al, 2020;Chan & Drasgow, 2001). Under a leader identity view, a person would first view themselves as a leader and then pursue a leadership opportunity to confirm their leader identity.…”
Section: Leader Identity and Motivations To Pursue Any Leadership Opp...mentioning
confidence: 99%